2021
DOI: 10.4081/jphr.2021.2434
|View full text |Cite
|
Sign up to set email alerts
|

Gaming, substance use and distress within a cohort of online gamblers

Abstract: Background: The fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) included Internet Gaming Disorder (IGD) as a tentative diagnosis and inquires for additional research. The research on gaming is inconsistent regarding measurement approach and diagnostic cut-offs. Some scholars suggest the core approach, accentuating some of the diagnostic criteria to avoid pathologizing harmless behavior. Also, the co-occurrence of gaming and other addictions, gambling in specifically, is frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
2
0
2
Order By: Relevance
“…We found that a small proportion of our patients had a problematic intake of alcohol or other drugs, to a comparable extent with the Wölfling et al (26) study. Other studies have for example shown a positive correlation between severity of GD and frequency of substance use (63)(64)(65). Studies have also shown that those who play under the influence of for example stimulants, Ecstasy/MDMA, sedatives or amphetamines spend more time gaming than non-substance users (62) and that high alcohol consumption is an antecedent to gaming disorder (66).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…We found that a small proportion of our patients had a problematic intake of alcohol or other drugs, to a comparable extent with the Wölfling et al (26) study. Other studies have for example shown a positive correlation between severity of GD and frequency of substance use (63)(64)(65). Studies have also shown that those who play under the influence of for example stimulants, Ecstasy/MDMA, sedatives or amphetamines spend more time gaming than non-substance users (62) and that high alcohol consumption is an antecedent to gaming disorder (66).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…Therefore, the 'core approach' applies a prioritization of the four core criterion, creating three categories of gamers: engaged gamers, problem gamers, and addicted gamers. This approach has been reported as clinically relevant as the created categories seem to relate to degrees of negative consequences as well as severity of addictive behavior (25,26).…”
Section: Gasamentioning
confidence: 99%
“…Selama COVID-19, tercatat adiksi internet pada masyarakat di Indonesia sebesar 14,4%, dimana penggunaan internet meningkat sebesar 52% dibandingkan dengan sebelum pandemi (Siste et al, 2020). Studi ini menunjukkan ukuran prevalensi gamer yang adiksi sebesar 1,2 persen (André et al, 2021). Di Korea Selatan persentase yang signifikan dari remaja ini melaporkan bahwa waktu mereka dihabiskan untuk game PC (45,5%) dan game seluler (56,6%) meningkat setelah wabah COVID-19 (Kim et al, 2021).…”
Section: Pendahuluanunclassified
“…Hasil studi ini didapatkan bahwa sebagian besar laki-laki mengalami adiksi game online. Studi yang sama telah dilakukan baru-baru ini dimana jenis kelamin laki-laki dikaitkan dengan game yang bermasalah dan adiktif (André et al, 2021). Laki-laki diangap sebagai faktor resiko pada adiksi game online (Hyun et al, 2015;Karaca et al, 2020).…”
Section: Hubungan Karakteristik Gender Dengan Adiksi Game Onlineunclassified